PENGARUH SPESIALISASI TUGAS DAN GAYA KEPEMIMPINAN TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN KUTAI TIMUR - Asmuniansyah . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Managing the human resources starts from the internal factor, placing the employees based on their academic knowledge and applying leadership style. Job specification and leadership style were becomes the pull factor to enhance work motivations. It also gives both good and bad impact to the improvement of work effectivity in the organization. Reaching work effectivity in the organization must be supported by job specification and applied leadership style.